2015
DOI: 10.1002/2015ja021446
|View full text |Cite
|
Sign up to set email alerts
|

Properties and geoeffectiveness of magnetic clouds during solar cycles 23 and 24

Abstract: We report on a study that compares the properties of magnetic clouds (MCs) during the first 73 months of solar cycles 23 and 24 in order to understand the weak geomagnetic activity in cycle 24. We find that the number of MCs did not decline in cycle 24, although the average sunspot number is known to have declined by ~40%. Despite the large number of MCs, their geoeffectiveness in cycle 24 was very low. The average Dst index in the sheath and cloud portions in cycle 24 was −33 nT and −23 nT, compared to −66 nT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
143
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(175 citation statements)
references
References 80 publications
(209 reference statements)
30
143
2
Order By: Relevance
“…In fact, there were only a dozen shocks measured at L1 between 2007 and 2008 (compared to 21 shocks in 1997 alone, for example). The lower number of geoeffective shocks‐sheaths during SC24 as compared to SC23 is consistent with results from studies investigating the interplanetary causes [ Gopalswamy et al , ] of geomagnetic storms. Gopalswamy et al [] showed that the lower number of storms in SC24 as compared to SC23 is a direct consequence of the lower interplanetary V B z , which in SC24 is 40% lower than the value in SC23 for magnetic clouds.…”
Section: Studysupporting
confidence: 87%
“…In fact, there were only a dozen shocks measured at L1 between 2007 and 2008 (compared to 21 shocks in 1997 alone, for example). The lower number of geoeffective shocks‐sheaths during SC24 as compared to SC23 is consistent with results from studies investigating the interplanetary causes [ Gopalswamy et al , ] of geomagnetic storms. Gopalswamy et al [] showed that the lower number of storms in SC24 as compared to SC23 is a direct consequence of the lower interplanetary V B z , which in SC24 is 40% lower than the value in SC23 for magnetic clouds.…”
Section: Studysupporting
confidence: 87%
“…The high total pressure inside the ICME and a low ambient total pressure can cause such a large expansion. On the other hand, the expansion factor VL/Vc = 1.28 is within the range of values reported for magnetic clouds in cycle 23 and cycle 24 (Gopalswamy et al 2015d). …”
Section: Cme Kinematics and Icme Observationssupporting
confidence: 86%
“…This requirement is in contradiction with the observation of the in-situ type II burst F3-H3. The fundamental and harmonic components were at 0.017 and 0.034 MHz, which yield a local plasma density of 3.6 cm , which is more than three times the highest expansion speed observed in cycle-24 magnetic clouds (Gopalswamy et al 2015d). The expansion speed is ~44% of the leading edge speed, while the typical value is ~6.3%.…”
Section: Cme Kinematics and Icme Observationsmentioning
confidence: 86%
“…Generally speaking, the lower total heliospheric pressure allowed the cycle 24 CMEs to expand more rapidly earlier in the event phase, resulting in larger CME widths for a given CME speed [Gopalswamy et al, 2014[Gopalswamy et al, , 2015a. As such, the effectiveness of a CME to produce a strong magnetic storm is reduced in part because of the diluted magnetic energy content attributed to the greater expansion and also because the lower IMF resulted in weaker compressed CME sheath fields [Gopalswamy et al, 2014[Gopalswamy et al, , 2015b. The weaker heliospheric conditions also affected the speeds of the CMEs.…”
Section: Discussionmentioning
confidence: 99%